Pengaruh Program Pemberdayaan Masyarakat Kota Kediri Terhadap Peningkatan Perekonomian Daerah - Novie Astuti Setianingsih; Aang Afandi; Wiwiek Kusumaning Asmoro (Gorontalo Accounting Journal, 2020)
This study aims to analyze the effect of the Community Empowerment Program (Prodamas) on improving the economy of the people of Kediri City which has been implemented in Kediri City. The method used in this research is descriptive quantitative by distributing questionnaires to 13 urban villages throughout Mojoroto District, Kediri City based on RT. Each RT was distributed 10 questionnaires, so a total of 130 questionnaires distributed. The results showed that the Community Empowerment Program (Prodamas) in the infrastructure sector (X1), the social sector (X2) and the economic sector (X3) had a significant positive effect on improving the regional economy (Y) of Kediri City.